1972
DOI: 10.1021/ic50114a023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of 10-phenoxarsine sulfide, an organoarsenical with planar phenoxarsine moieties

Abstract: The crystal and molecular structure of 10-phenoxarsine sulfide, (Ci2H8OAs)2S, has been determined by single-crystal X-ray diffraction methods. The unit cell is triclinic: a = 9.033 (1) Á, b = 11.435 (2) Á, c = 14.114 (3) A, a -127.83 (3)°, ß = 112.10 (2)°, and y = 84.36 (1)°. The Delauney cell has a = 9.033 (1) A, b = 11.435 (2) Á, c = 13.597 (3) Á, a -124.85 (3)°, ß = 105439 (2)°, r = 95.64 (1)°, with ámeas<¡ = 1.61 (1) g cm"3 and ¿cai"d (for Z = 2) = 1.640 (3) g cm"3. The space group is PI (G1; No. 2), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The phenoxarsine group is very flexible and can adopt either a planar or a folded geometry; the dihedral angles reported so far lie in the range of 150−180°. In O(C 6 H 4 ) 2 AsS(S)PR 2 (R = Me, Et), this angle is 176.1 and 173.1°, and the known bis(phenoxarsine) compounds O(C 6 H 4 ) 2 As−E−As(C 6 H 4 ) 2 O (E = S, Se) also contain two nearly planar phenoxarsine moieties (dihedral angles: 175.2 and 175.8° for E = S, and 173.9 and 176.0° for E = Se). In contrast, the phenoxarsine moieties in 1 – 4 exhibit a folded (butterfly) arrangement with dihedral angles of 151.20 and 150.07° in 1 , 153.70° in 2 , 162.96° in 3 , and 163.40° in 4 , close to the values reported for O(C 6 H 4 ) 2 AsCl (156.3°), O(C 6 H 4 ) 2 AsS 2 CN(CH 2 CH 2 ) 2 (155.2°), the phenoxarsin-10-yl derivative of 2-aminocyclopent-1-ene-1-carbodithioic acid O(C 6 H 4 ) 2 AsS(S)CC 5 H 6 NH 2 -2 (150.3°), O(C 6 H 4 ) 2 AsS 2 PPh 2 (154.4°), and O(C 6 H 4 ) 2 AsOAs(C 6 H 4 ) 2 O (157.6 and 176.0°), or in the adduct of SbCl 5 with 10-chlorophenoxarsine oxide {O(C 6 H 4 ) 2 AsClOSbCl 5 } (167.7°) .…”
Section: Discussionmentioning
confidence: 99%
“…The phenoxarsine group is very flexible and can adopt either a planar or a folded geometry; the dihedral angles reported so far lie in the range of 150−180°. In O(C 6 H 4 ) 2 AsS(S)PR 2 (R = Me, Et), this angle is 176.1 and 173.1°, and the known bis(phenoxarsine) compounds O(C 6 H 4 ) 2 As−E−As(C 6 H 4 ) 2 O (E = S, Se) also contain two nearly planar phenoxarsine moieties (dihedral angles: 175.2 and 175.8° for E = S, and 173.9 and 176.0° for E = Se). In contrast, the phenoxarsine moieties in 1 – 4 exhibit a folded (butterfly) arrangement with dihedral angles of 151.20 and 150.07° in 1 , 153.70° in 2 , 162.96° in 3 , and 163.40° in 4 , close to the values reported for O(C 6 H 4 ) 2 AsCl (156.3°), O(C 6 H 4 ) 2 AsS 2 CN(CH 2 CH 2 ) 2 (155.2°), the phenoxarsin-10-yl derivative of 2-aminocyclopent-1-ene-1-carbodithioic acid O(C 6 H 4 ) 2 AsS(S)CC 5 H 6 NH 2 -2 (150.3°), O(C 6 H 4 ) 2 AsS 2 PPh 2 (154.4°), and O(C 6 H 4 ) 2 AsOAs(C 6 H 4 ) 2 O (157.6 and 176.0°), or in the adduct of SbCl 5 with 10-chlorophenoxarsine oxide {O(C 6 H 4 ) 2 AsClOSbCl 5 } (167.7°) .…”
Section: Discussionmentioning
confidence: 99%
“…Our CSD search showed that, in an appreciable number of crystals, the As···O distance is longer than the sum of the vdW radii of As and O atomic basins, 3.38 Å. These include, to list just three, crystals such as C 28 H 36 As 4 Cl 2 O 16 Pd ( r (As···O) = 3.773 Å and ∠Pd–As···O = 171.6°, CSD ref: JIZMIP [ 191 ]), C 8 H 11 AsBBr 2 NO 5 WPd ( r (As···O) = 3.786 Å and ∠Br–As···O = 159.2°, CSD ref: JOJZEO [ 192 ]), and 10-phenoxarsine sulfide ( r (As···O) = 3.666 Å and ∠S–As···O = 150.1°, CSD ref: POXARS [ 184 ]).…”
Section: Arsenic In Crystalsmentioning
confidence: 99%
“… Examples showing As···N pnictogen bonds in the crystals of ( a ) ((6-Me(C 4 H 3 N)NAsCl) 2 bis( μ 2 -(6-methyl-2-pyridyl)amido)-syn-dichloro-di-arsenic(III) [ 181 ]; ( b ) (CH 2 N(CH 3 )) 2 AsCl, 2-chloro-1,3-dimethyl-1,3-diaza-2-arsolidine [ 183 ]; ( c ) (Ph 2 NH)AsCH 3 , 5-methyl-5,10-dihydrophenarsazine [ 184 ]; and ( d ) (Ph 2 NH)As(3-MeOPh), 5-(3-methoxyphenyl)-5,10-dihydrophenarsazine [ 185 ]. Selected atom type is shown in ( b – d ).…”
Section: Figures Schemes and Tablementioning
confidence: 99%